2015
DOI: 10.1002/bdm.1855
|View full text |Cite
|
Sign up to set email alerts
|

Allais from Experience: Choice Consistency, Rare Events, and Common Consequences in Repeated Decisions

Abstract: The Allais Paradox is a well-known bias in which people's preferences result in contradictory choices between two normatively identical gamble pairs. Studies have shown that these preference reversals depend on how information is described and presented. In an experiment, we investigate the Allais gambles in several formats including an experiential paradigm, where participants make selections from two blank buttons and get an outcome as a result of a draw from distributions of outcomes in the selected gamble.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Results from Experiment 1 expand demonstrations of biases originally found with descriptive scenarios that become weaker or disappear when choices are made from experience (Dutt et al, 2013;Gonzalez, 2013;Harman & Gonzalez, 2015). We also find that, the description-experience gap (e.g., Gonzalez & Dutt, 2011;Hertwig, 2012;Hertwig & Erev, 2009), disappears, and instead, we find consistent risk behavior for gains and losses, in contrast with the reversed four-fold pattern (Hertwig, 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results from Experiment 1 expand demonstrations of biases originally found with descriptive scenarios that become weaker or disappear when choices are made from experience (Dutt et al, 2013;Gonzalez, 2013;Harman & Gonzalez, 2015). We also find that, the description-experience gap (e.g., Gonzalez & Dutt, 2011;Hertwig, 2012;Hertwig & Erev, 2009), disappears, and instead, we find consistent risk behavior for gains and losses, in contrast with the reversed four-fold pattern (Hertwig, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…While in descriptive decisions, people often act as if low-probability outcomes were more probable than they really are (i.e., they are overweighted), people in experiential decisions act as if low probability outcomes were less probable than they really are (i.e., they are underweighted), resulting in a phenomenon coined as the description-experience gap (Barron & Erev, 2003;Camilleri & Newell, 2009;Hertwig, Barron, Weber, & Erev, 2004;Hertwig & Erev, 2009). More generally, recent research suggests that well-known biases originally demonstrated with descriptive scenarios may not exist or might be weaker when people make decisions from experience (Dutt, Arlo-Costa, Helzner, & Gonzalez, 2013;Gonzalez, 2013;Harman & Gonzalez, 2015).…”
Section: Gains Versus Losses In Decisions From Experiencementioning
confidence: 99%
“…Psychologists and economists (e.g. Hertwig et al, 2004;Harman & Gonzalez, 2015) more recently found that decision-making does not always follow prospect theory. Particularly, for rare events, the costs may not be overweighed.…”
Section: Anchoring Effectmentioning
confidence: 99%
“…In particular, a decision maker may choose an option that "looks better" (e.g., if salient comparisons make one alternative more visually appealing than the other), or choose an option that "feels better" (e.g., selecting the option that elicits a more positive or less aversive affective response), or choose the option that is "calculated as better" (e.g., which can be justified by logical reasoning or calculation). If the "looks better" heuristic is predominantly used in the choice task (as it permits visual comparisons between alternatives), if the "feels better" heuristic is predominantly used in the happiness task (as it may involve affect), and if the "calculated as better" heuristic is predominantly used in the pricing task (as it may involve calculation), that would explain both the response mode reversals for the common ratio effect in our experiment and the framing reversals for the common ratio effect observed by Harless (1992) and Harman and Gonzalez (2015). These three heuristics do not require a multiple-systems perspective, although they are consistent with Kahneman's (2003) framework, which distinguishes between three systems: perception, intuition ("System 1"), and reasoning ("System 2").…”
Section: Discussionmentioning
confidence: 73%